Noteworthy sequelae after COVID-19 pneumonia in a patient with heart failure due to cardiomyopathy. Issue 4 (April 2023) - Utsugi, Yui; Kuwata, Shingo; Doi, Shunichi; Sato, Yukio; Suzuki, Norio; Izumo, Masaki; Harada, Tomoo; Ishibashi, Yuki; Akashi, Yoshihiro J.
Abstract: Coronavirus disease 2019 (COVID-19) is endemic worldwide. Cardiovascular disease, particularly myocarditis, is one of the most common comorbidities in patients with COVID-19. However, heart failure due to COVID-19-triggered cardiomyopathy is not well understood. Additionally, "pseudo" heart failure symptoms have been reported in patients with a compensated condition, in which the heart works well enough that symptoms are unnoticeable or very easy to manage. Here, we report a case of heart failure due to cardiomyopathy in a patient with COVID-19 and postural orthostatic tachycardia syndrome after heart failure treatment. Learning objective: Postural orthostatic tachycardia syndrome (POTS) symptoms after coronavirus disease 2019 may be mistaken for heart failure symptoms; thus, it is essential to suspect POTS when symptoms such as shortness of breath and palpitations are noted upon standing, along with the relevant physical findings.